Ageing and autobiographical memory for emotional and neutral events - St. Jacques, Peggy L. (2007)
We investigated age-related effects in recall of emotional and neutral autobiographical memories. Protocols were scored according to episodic and non-episodic detail categories using the Autobiographical Interview. Young adults recalled a greater number of episodic details compared to older adults, whereas older adults recalled more semantic details, replicating previous findings. Both young and older adults’ emotional memories contained more overall detail than neutral ones, with the enhancement from emotion-specific to episodic details, but this did not alter the effect of age group on the pattern of episodic and semantic details. However, the age effect on episodic details was attenuated for neutral autobiographical memories. The findings suggest that age differences for emotional autobiographical recollection might reflect a more general pattern of age-related changes in memory, with impaired recall of episodic components and relative sparing of semantic aspects of autobiographical memory in older adults when compared to young adults.